2022
DOI: 10.3390/ijerph191811582
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Regulation for Ecological Protection and Remediation: A Case Study of the Irtysh River Basin, China

Abstract: Hydrological processes play a key role in ecosystem stability in arid regions. The operation of water conservancy projects leads to changes in the natural hydrological processes, thereby damaging the ecosystem balance. Ecological regulation is an effective non-engineering measure to relieve the influence of water conservancy projects on ecosystems. However, there are still some problems, such as an insufficient understanding of hydraulic processes and difficulty evaluating the application effects. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…During the model validation stage, the NSE values are 0.93, 0.85, and 0.94 for the respective sites, which further confirmed the rationality of the parameter values. Additionally, the accuracy of the model is further confirmed by comparing the inundation area derived from the model simulation results with remote sensing images, showing an error of less than 15% [52]. Moreover, the comparison between the calculated and observed hydrographs for the wet periods in 2016 and 2017 at the three sites (Burqin, Sarbulak, Halagou Mudao Bridge) is depicted in Figure 8, demonstrating a strong agreement.…”
Section: The 2d Hydrodynamic Modelmentioning
confidence: 52%
See 2 more Smart Citations
“…During the model validation stage, the NSE values are 0.93, 0.85, and 0.94 for the respective sites, which further confirmed the rationality of the parameter values. Additionally, the accuracy of the model is further confirmed by comparing the inundation area derived from the model simulation results with remote sensing images, showing an error of less than 15% [52]. Moreover, the comparison between the calculated and observed hydrographs for the wet periods in 2016 and 2017 at the three sites (Burqin, Sarbulak, Halagou Mudao Bridge) is depicted in Figure 8, demonstrating a strong agreement.…”
Section: The 2d Hydrodynamic Modelmentioning
confidence: 52%
“…The time step and Manning's roughness coefficient of the hydrodynamic model plays a crucial role in determining the simulation accuracy, and their values can be determined during the model calibration phase by trial and error. A comprehensive description of the model establishment, calibration, validation, and application of TELEMAC-2D in the study area can be found in reference [52].…”
Section: The Establishment Of Hydrodynamic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies have found [46] that the pollution level of the upper reaches of the Irtysh River is low, and the cross-border runoff does not have the characteristics of serious pollution. This may be due to increased rainfall and reduced permafrost volume, coupled with the effective operation of large dams and reservoirs in the Irtysh River Basin in China and the implementation of water-saving technologies, which ensured the water level in the basin [47] and weakened the impact of polluted water in the Ulungu River, ensuring the health of the river. However, the water quality of the Irtysh River in East Kazakhstan is poor, which may be mainly due to heavy metal and nuclear pollution caused by previous industries in the area [48].…”
Section: Water Quality Evaluationmentioning
confidence: 99%
“…Within the IRB, the Irtysh River is the only river in China that flows into the Arctic Ocean. It originates from the southwestern slope of the Altai Mountains in China, and its water volume ranks second in XJ following the Ili River (Liu et al, 2017;Wang et al, 2022). The NSTM consists of small-and medium-sized rivers and is the most economically developed area in XJ, with the sharpest contradiction between the supply and demand of water resources (Sun et al, 2022).…”
Section: Study Areamentioning
confidence: 99%